Histone Deacetylase 1 Depletion Activates Human Cardiac Mesenchymal Stromal Cell Proangiogenic Paracrine Signaling Through a Mechanism Requiring Enhanced Basic Fibroblast Growth Factor Synthesis and Secretion. Issue 7 (July 2017) - Moore, Joseph B.; Zhao, John; Fischer, Annalara G.; Keith, Matthew C.L.; Hagan, David; Wysoczynski, Marcin; Bolli, Roberto
Abstract : Background: Cardiac mesenchymal cell (CMC) administration improves cardiac function in animal models of heart failure. Although the precise mechanisms remain unclear, transdifferentiation and paracrine signaling are suggested to underlie their cardiac reparative effects. We have shown that histone deacetylase 1 (HDAC1) inhibition enhances CMC cardiomyogenic lineage commitment. Here, we investigated the impact of HDAC1 on CMC cytokine secretion and associated paracrine‐mediated activities on endothelial cell function. Methods and Results: CMCs were transduced with shRNA constructs targeting HDAC1 (shHDAC1) or nontarget (shNT) control. Cytokine arrays were used to assess the expression of secreted proteins in conditioned medium (CM) from shHDAC1 or shNT‐transduced CMCs. In vitro functional assays for cell proliferation, protection from oxidative stress, cell migration, and tube formation were performed on human endothelial cells incubated with CM from the various treatment conditions. CM from shHDAC1‐transduced CMCs contained more cytokines involved in cell growth/differentiation and more efficiently promoted endothelial cell proliferation and tube formation compared with CM from shNT. After evaluating key cytokines previously implicated in cell‐therapy–mediated cardiac repair, we found that basic fibroblast growth factor was significantly upregulated in shHDAC1‐transduced CMCs. Furthermore, shRNA‐mediated knockdown of basic fibroblast growth factor in HDAC1‐depleted CMCs inhibited the effects of shHDAC1 CM in promoting endothelial proliferation and tube formation—indicating that HDAC1 depletion activates CMC proangiogenic paracrine signaling in a basic fibroblast growth factor–dependent manner. Conclusions: These results reveal a hitherto unknown role for HDAC1 in the modulation of CMC cytokine secretion and implicate the targeted inhibition of HDAC1 in CMCs as a means to enhance paracrine‐mediated neovascularization in cardiac cell therapy applications.